1994
DOI: 10.3109/09513599409028459
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, phosphorus and magnesium intakes correlate with bone mineral content in postmenopausal women

Abstract: Qualitative and quantitative differences in the dietary habits of postmenopausal women were studied to assess their influence on bone health and osteoporosis. A total of 194 postmenopausal women were studied with forearm DEXA densitometry. 70 were osteoporotic and 124 served as controls. Women had been menopausal for 5-7 years, and had never been treated with hormone replacement or drug therapy. A 3-day dietary recall was completed on Sunday, Monday and Tuesday after the examination: the results were processed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…Recent studies have suggested that diets high in magnesium and potassium may be bene®cial for bone mass maintenance in elderly (Tucker et al, 1999), postmenopausal women (Tranquilli et al, 1994) and premenopausal women (New et al, 1997). The role of phosphorus is more controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that diets high in magnesium and potassium may be bene®cial for bone mass maintenance in elderly (Tucker et al, 1999), postmenopausal women (Tranquilli et al, 1994) and premenopausal women (New et al, 1997). The role of phosphorus is more controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive phosphorus from carbonated beverages may increase the risk of adolescent fractures (Wyshak & Frisch, 1994) as well as impair bone homeostasis (Calvo, 1994). However, phosphorus supplementation leads to short-term increases in growth in preterm neonates (Faerk et al, 2000) while phosphorus intake is positively associated with BMD in young women (Teegarden et al, 1998) and postmenopausal women (Tranquilli et al, 1994). There have been few reports relating fat intake to BMD.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is supported by observations of increased bone mineral density (Abraham & Grewal 1990;Stendig-Lindberg et al, 1993), as well as relief of backpain and movement restrictions by Mg supplementation in osteoporotic patients (Driessens et al, 1990). Also, a number of dietary studies have consistently suggested that bone mineral density is greater in people with high intakes of Mg and potassium (Freudenheim et al, 1986;Angus et al, 1988;Tranquilli et al, 1994;New et al, 1997;Tucker et al, 1999). There is limited research into the impact of supplementary Mg on biochemical markers of bone turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary and serum, but not red cell, magnesium were generally lower among the elderly with osteoporosis 45,86,109 and among healthy older adults, magnesium intake was positively associated with BMD, BMC and bone mass 86,[110][111] , with an intake of >422.5mg/d vs <206.5 mg/d improving BMD 110 . A large multiethnic study found that this association may apply to older whites but not blacks 112 .…”
Section: Bonementioning
confidence: 99%
“…Results of adult human studies show mixed results for associations between total phosphorus intake and osteoporosis or fractures [84][85][86] , although inorganic phosphorus intake from colas induced a higher incidence of osteopenia and lower BMD among women only; since this was not seen with other soft drinks it is likely to be attributable to phosphoric acid 64 . Among healthy women, dietary and serum phosphorus were generally not associated with BMD or markers of bone formation or resorption 45,85,87 .…”
Section: Bonementioning
confidence: 99%